Motivation, Perception and Preference of Tourists on Mangrove Tourism Destinations in Sedari Village, Cibuaya District, Karawang Regency - Andini Anggia Septyaningtyas; Nadine Azzahra Syah; Myrza Rahmanita; Nurbaeti Nurbaeti (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
Karawang Regency has many tourist destinations and villages, one of which is Sedari Village, which has a natural potential to develop mangrove forests. Referring to Law No. 10 of 2009 concerning tourism development which must pay attention to the needs of tourists in the process of its implementation, it is necessary to conduct a study related to Motivation, Perceptions, and Tourist Preferences to become a reference for the development of mangrove tourism in Sedari Village. This study uses a descriptive quantitative approach, data obtained through interviews and questionnaires. The data processing method uses validity test, reliability test, and Importance Performance Analysis. The study results show four indicators of motivation that encourage tourists to visit the village mangrove tourism, then the average value of perception is 2.